PENGARUH PENGGUNAAN GADGET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 3 KOTA JAMBI - Agustianingsih Agustianingsih; Redi Indra Yudha (Universitas Batanghari Jambi, 2020)
This study aims to determine (1) an overview of the use of the MYOB application in computer accounting subjects at SMK Negeri 1 Bayung Lencir. (2) An overview of student learning outcomes in computer accounting subjects at SMK Negeri 1 Bayung Lencir. (3) the influence of the use of MYOB applications in computer accounting subjects on student learning outcomes at SMK Negeri 1 Bayung Lencir. The results showed that (1) for the use of MYOB applications obtained a TCR of 65.15% in the Fairly Good category. (2) The results of the calculation show that the learning outcomes of students in computer accounting subjects who score less than 7.5 are 40 students, while students who score above 7.5 are 41 students. (3) from the results of the calculation of simple regression analysis, there is an effect of the use of the MYOB (X) application on learning outcomes (Y) of 71.1%, as evidenced by the results of the t-test, which is 8.994, is greater than the t table, which is 1.644. Yang stated that Ha's knowledge was accepted and Ho was rejected